Implementing corporate sustainability projects - an organizational cybernetic perspective (2015)
Currently , firms are starting to translate the rhetoric related to sustainable development principles on which global development is being founded to concrete corporate and business strategies, processes and actions. Projects targeting economic, social and environmental dimensions (or what is known as corporate sustainability projects) are being structured and implemented. These actions imply for firms the integration of social and environmental subjects into strategies and operations while remaining financially profitable. In fact. firms need to adjust the whole organizational system Including processes, procedures, physical arrangement, strategy, culture values, visions, philosophies, or policies actions that have demonstrated to be difficult and complex to undergo This dissertation presents how systems thinking approaches, specifically Beer's Viable Systems Model (VSM) and Dyson's Strategy Development Process (SDP), together with strategic management knowledge regarding dynamic capabilities has inspired instruments to support the endeavor of corporate sustainability Project implementation. Based on recent research that had advanced the ideas about viability as the principal requisite to achieve sustainability, this thesis Introduces an adjusted version of the "Methodology to support organizational self-transformation" and a case study where this methodology was used to support the implementation of a corporate sustainability project showing promising results for future corporate sustainability actions